Historia, memoria y víctimas de la violencia política - Pérez Pérez, José Antonio (Huarte de San Juan. Geografía e Historia, 2015)
Over more than twenty years the Institute of Social History Valentín de Foronda has developed an intense academic activity. At this time his research group has promoted various lines of work. One of the most important has been focused in recent years in the field of memory and its relationship with political violence and victims, one of the most controversial in the recent history of the Basque Country issues. From various activities: symposiums, seminars, research projects and a large number of publications, our group has analyzed the role played by memory and political violence form a perspective open to other professional disciplines. This article is just an overview of the most important contributions made by the Instituto Foronda over the last two decades in this field.